Mathematical description of a river absorption capacity on the example of the middle Warta catchment - Wilk, Paweł; Orlińska-Woźniak, Paulina; Gębala, Joanna (Oficyna Wydawnicza Politechniki Wrocławskiej, 2018)
The paper presents a mathematical description of a module to determine the river absorption capacity (RAC), which is an extension of the Macromodel DNS/SWAT developed in IMGW-PIB. The balance equations of pollution loads are presented, as well as the mathematical description of the retention of pollutants, taking into account concentrations and loads of pollutants in selected river profiles. The developed mathematical module mRAC was tested in the Warta catchment between river calculation profiles Nowa Wieś Podgórna and Oborniki for total nitrogen (TN) and total phosphorus (TP).
Environment Protection Engineering. Vol. 44, 2018, nr 4, s. 99-116
Keywords: ochrona środowiska; inżynieria środowiska; czasopisma